login
E.g.f. satisfies A(x) = 1 - x*A(x)^2*log(1 - x*A(x)^2).
6

%I #10 Mar 16 2024 11:56:45

%S 1,0,2,3,104,630,19944,259560,8718464,185086944,6914815200,

%T 206059083120,8700740615808,332779651158240,15916427365716864,

%U 738672634596405600,39847940942657495040,2163098542598925281280,130682368989193123952640

%N E.g.f. satisfies A(x) = 1 - x*A(x)^2*log(1 - x*A(x)^2).

%F a(n) = n! * (2*n)! * Sum_{k=0..floor(n/2)} |Stirling1(n-k,k)|/( (n-k)! * (2*n-k+1)! ).

%o (PARI) a(n) = n!*(2*n)!*sum(k=0, n\2, abs(stirling(n-k, k, 1))/((n-k)!*(2*n-k+1)!));

%Y Cf. A371227, A371228, A371230.

%Y Cf. A371121, A371231.

%Y Cf. A370993.

%K nonn

%O 0,3

%A _Seiichi Manyama_, Mar 15 2024